2016
DOI: 10.18632/aging.101031
|View full text |Cite
|
Sign up to set email alerts
|

PPARβ/δ selectively regulates phenotypic features of age-related macular degeneration

Abstract: Peroxisome proliferator-activated receptor-β/δ (PPARβ/δ) is a nuclear receptor that regulates differentiation, inflammation, lipid metabolism, extracellular matrix remodeling, and angiogenesis in multiple tissues. These pathways are also central to the pathogenesis of age-related macular degeneration (AMD), the leading cause of vision loss globally. With the goal of identifying signaling pathways that may be important in the development of AMD, we investigated the impact of PPARβ/δ activation on ocular tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 63 publications
1
44
0
Order By: Relevance
“…Genetic disruption of Pparβ / δ and specific PPARβ/δ antagonists have previously been shown to attenuate laser-induced CNV in mice [ 21 ]. Surprisingly, our study showed no detectable PPARβ/δ protein in the choroid/retinal pigment epithelium (RPE) fraction of C57BL/6 mouse eyes ( Figure 1 a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic disruption of Pparβ / δ and specific PPARβ/δ antagonists have previously been shown to attenuate laser-induced CNV in mice [ 21 ]. Surprisingly, our study showed no detectable PPARβ/δ protein in the choroid/retinal pigment epithelium (RPE) fraction of C57BL/6 mouse eyes ( Figure 1 a).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study reported a reduced lesion size in Pparβ/δ −/− mice subjected to laser-induced CNV [ 21 ]. Surprisingly, our study could not detect PPARβ/δ in the RPE/choroid fraction of C57BL/6 mouse eyes.…”
Section: Discussionmentioning
confidence: 99%
“…PPAR-b/d modulation seems to play different roles in dry AMD and neovascular AMD models. Pharmacological inhibition of PPAR-b/d signalling in vitro on RPE cells or in vivo in the mouse laser-induced choroidal neovascularization model, limited angiogenesis (54), but exacerbated signs of dry AMD. Conversely, activation of PPAR-b/d reduced lipid accumulation in RPE cells in vitro (a symptom in intermediate dry AMD) [55].…”
Section: Discussionmentioning
confidence: 99%
“…RNA from ARPE-19 cells was generously provided by Goldis Malek (Duke University) and was isolated as previously described. 36 RNA (150 ng) from each sample was used to synthesize cDNA using ProtoScript II Reverse Transcriptase (NEB, Ipswich, MA, USA). Each RT-PCR reaction contained 7.5 ng cDNA, 200 nmol/L each primer, and 12.5 μL iQ SYBR green supermix (Bio-Rad) in 25 μL total volume.…”
Section: Methodsmentioning
confidence: 99%